Interaction mechanism of endogenous PP2A inhibitor protein ENSA with PP2A - Thapa Chandan; Roivas Pekka; Haataja Tatu; Permi Perttu; Pentikäinen Ulla (WILEY, 2025)
The vast diversity of protein phosphatase 2A (PP2A) holoenzyme composition ensures its multifaceted role in the regulation of cellular growth and signal transduction. In several pathological conditions, such as cancer, PP2A is inhibited by endogenous inhibitor proteins. Several PP2A inhibitor proteins have been identified, one of which is alpha-endosulfine (ENSA). ENSA inhibits PP2A activity when it is phosphorylated at Ser67 by Greatwall (Gwl) kinase. The role of ENSA in PP2A inhibition is rather well characterized, but knowledge of the mechanism of inhibition is scarce. In this study, we have performed comprehensive structural characterization of ENSA, and its interaction with PP2A A- and various B56-subunit isoforms by combining NMR spectroscopy, small-angle X-ray scattering (SAXS) and interaction assays. The results clearly indicate that ENSA is an intrinsically disordered protein containing three transient alpha-helical structures. ENSA was observed to interact PP2A mainly via A-subunit, as the affinity with the A-subunit is significantly stronger than with any of the B56 subunits. Based on our results, it seems that ENSA follows the dock-and-coalesce mechanism in associating with PP2A A-subunit. Taken together, our results provide an essential structural and molecular framework to understanding molecular bases of ENSA-mediated PP2A inhibition, which is crucial for the development of new therapies for diseases linked to PP2A inhibition.